Insolation-driven 100,000-year glacial cycles and hysteresis of ice-sheet volume by Ayako Abe-Ouchi et al., Nature 500 - Cranganu, Constantin (Journal of Scientific Exploration, 2014)
One hundred years ago the German meteorologist Alfred Wegener started a scientific revolution that was probably the most important of the 20th century: plate tectonics. In the same year (1912) in Serbia, Milutin Milanković, a civil engineer turned professor of mathematics at the University of Belgrade, published the paper that would forever change the way we look at and attempt to understand climate changes through our understanding of the so-called Milanković cycles. For many years climatologists and geologists could not explain the causes of ice ages on Earth. Various hypotheses were offered, but all failed to explain how ice sheets grew and then melted many times in the geologic past. Milanković’s idea was to put the Sun at the center of his theory of ice ages. He proposed three orbital cycles of Earth: eccentricity of elliptic orbit (100,000-year cycle), axial tilt of rotation axis (obliquity) (41,000-year cycle—from 22.1° to 24.5°; presently, the Earth’s tilt is 23.5°), and precession of equinoxes (23,000-year cycle). Because each cycle works on a different timescale, their combined effects have a variable influence on the amount of solar energy received by the Earth. In short, Milanković’s theory proposes that summer insolation at high northern latitudes (beyond 55°N) drives the glacial–interglacial cycles, and the summer insolation is, in turn, linked to eccentricity, obliquity, and precession cycles.